Cold Agglutinin Disease–Associated Transient Ischemic Attack, Non-ST Elevation Myocardial Infarction, and Skin Necrosis: A Case Report - David Aziz; Rachel Parks; Ashley Barras; George Mina; Christopher Haas; Suraj Jande (Annals of Internal Medicine: Clinical Cases)
Cold agglutinin disease is a rare autoimmune hemolytic anemia that preferentially affects female patients and is more common in those older than 60 years. The pathophysiology involves IgM autoantibodies against erythrocytes in areas of the body at cooler temperatures, causing thrombosis and hemolysis. We present the case of a 66-year-old man who was found to have cold agglutinin disease and initially presented with altered mental status, stroke-like symptoms, and non-ST elevation myocardial infarction. Overnight, he also developed striking soft-tissue necrosis of his bilateral feet due to microvascular occlusion. His altered mentation and cardiac ischemia completely resolved; however, he eventually required bilateral phalangeal amputation.